Evaluation of an enzymatic hydrolysate of spray dried red tilapia viscera (Oreochromis spp) as a source of bioactive peptides (2020)
ABSTRACT: Increased global fish consumption generates large amounts of by-products from industrial aquaculture processing. This work studied the enzymatic hydrolysis of the viscera of red tilapia (Oreochromis spp.), and we found product inhibition and thermal inactivation of the enzyme. The reaction on a 10-fold scale (5 L) was modeled using neural networks with a high prediction (R2 = 0.999). We used response surface methodology to maximize the degree of hydrolysis (DH), and the antioxidant activity determined by ABTS, FRAP, and iron-chelating capacity of tilapia hydrolysate. Tilapia hydrolysate showed a high solubility and emulsifying but low foaming capacity. The most abundant amino acids in tilapia hydrolysate are Glx, Asx, and Gly. The hydrophobic amino acids correspond around 39% of the total of amino acids. The molecular weight distribution of hydrolysate showed low molecular weight peptides with a notorious amount of around 336 Da. The antioxidant activity determined by ABTS, FRAP, and the iron-chelating activity and the angiotensin-converting enzyme (ACE) inhibitory activity of tilapia hydrolysate is considered promising compared with other hydrolysates. Furthermore, we propose a new proof-of-concept for the screening of metal chelating peptides in hydrolysates using the switchSENSE®. Tilapia hydrolysate showed a comparable association rate (kon) with some of the synthetic peptides studied known from the literature as a complex metal ion. We also study the effect of spray drying conditions on the antioxidant activity of the hydrolysate. A high inlet air temperature and fast feed flow decrease the moisture and increase the drying rate and antioxidant activity of the spray-dried hydrolysate. Considering the problems of hydrophobicity, hygroscopicity, low bioavailability, and unpleasant sensory characteristics of the hydrolysates, we selected composite soy-rapeseed lecithin to encapsulate the tilapia hydrolysate by liposomes. We study three concentrations of hydrolysate to be encapsulated and we found that the liposomes loaded with 20% of hydrolysate (SRLH20) had smaller particle size, and higher values for ABTS and iron-chelanting activity, while liposomes loaded with 5% of hydrolysate (SRLH5) had higher electronegative ζ potential and entrapment efficiency. Charged amino acid residues, such as Glx (-) and Arg (+), had high encapsulation percentages. Finally, to increase the shelf life of the liposomes loaded with hydrolysate, we use trehalose as a stabilizer. Stability during storage showed that liposomes stored at 4 °C had lower values of particle size, polydispersity index (PDI), water activity, and higher solubility than those stored at 23 °C. Additionally, antioxidant activity was not affected by storage conditions. After simulated gastrointestinal digestion, the antioxidant and ACE inhibition activities of the hydrolysate tended to increase. Transmission electron microscopy analysis shows that vesicles retain their shape and membrane after 11 months of storage at 4 °C.